Introduction of a teaching module on intravenous drug administration and communication skills in pharmacology - Bhanwra, Sangeeta; Kumar, Rajiv; Garg, Gaurav (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pharmacology practicals mainly focus on increasing the knowledge component but teaching on psychomotor and soft skills is largely lacking. Teaching correct method of intravenous drug administration and the communication skills about drug therapy in Pharmacology practical classes can help in minimizing the errors in drug administration and improving the patient compliance and adherence to the therapy. Objectives of this study were teaching module on intravenous drug administration and communication skills to undergraduate students in Pharmacology and to evaluate the perceptions of students and teachers towards the new teaching module. Methods: Correct methods of intravenous drug administration were demonstrated in practical classes. Role play was done to teach about communication skills regarding right method of using an inhaler and also about prescribing the correct dosage regimens. Perceptions of students and teaching staff members were collected on the teaching module. Results: Almost all of the students (>96 %) were of the opinion that learning correct drug administration methods and communication skills was relevant to the future practice and 95% students felt that after the role play sessions, they were better equipped in communicating with the patients about the medication use and were in favour of teaching these to all the medical students. Conclusions: Our study concludes that the teaching module on intravenous drug administration and communication skills was well accepted by both the teaching staff and the students and was found feasible and relevant to be introduced in the curriculum by both of them.